Amboy : recipes from the Filipino-American dream - Cailan, Alvin; Cuerdo, Alexandra; Choung, Susan (Houghton Mifflin Harcourt, 2020)
"Filipino recipes from the creator of the legendary Eggslut in LA, host of the hit online series The Burger Show, and the most prominent Filipino chef in the US"--